Pengaruh Tindakan Perawatan Luka Terhadap Proses Penyembuhan Luka Ulkus Diabetikum pada Pasien DM di Puskesmas Kota Rantauprapat - Eva Haryana Elisa Panjaitan (Universitas Respati Indonesia, 2021)
Diabetes mellitus is a serious problem and continues to grow globally. Diabetes mellitus sufferers who experienced injuries to their feet really need proper wound care techniques to avoid amputation. . The study aimed to determine the effect of wound care measures on the healing process of diabetic ulcer wounds in diabetes mellitus (DM) patients at the Rantau Prapat city health center. This study used a qualitative descriptive research design conducted with an interview approach. There were 6 informants consisting of 2 informants with diabetic ulcer wounds, 4 health workers. Data analysis used a qualitative descriptive analysis. From the results of the study was known that knowledge of how wound care is still low, the attitude of informants is afraid and worried so that they are not disciplined in coming to the health center according to the predetermined schedule, as well as education and also health facilities greatly influence the act of treating wound with conventionally and with care modern wounds.